The Hypoglycemic Potential of Endophytic Lactobacillus kunkeei, Isolated from Dandelion Flowers in Rats - Zaripova, Mekhrangiz; Vypova, Nataliya; Amirsaidova, Dildora; Bekmurodova, Gullola; Aripov, Takhir; Gayibov, Ulugbek; Miralimova, Shakhlo; Gayibova, Sabina (Journal of Basic and Applied Pharmacology, 2022)
Blood glucose level control is a widely used approach, as diabetes mellitus is increasing worldwide. Lactobacillales have recently attracted the greatest attention due to their diabetes alleviating effects. Therefore, the current study was designed with the objective to evaluate the antidiabetic potential of entophytic Lactobacillus kunkei isolated from local Taraxacum kok-saghyz L. in glucose-, adrenaline-, and alloxan-induced diabetic rat models. In this study, the L.kunkeei strain was isolated from local Taraxacum kok-saghyz L. (locality Tashkent, Uzbekistan). Blood glucose in glucose-, adrenaline-, alloxan-induced and MDA level in alloxan-induced diabetic rats under L. kunkeei pretreatment was evaluated. In the current study, blood glucose levels were significantly improved by L. kunkeei in glucose-, adrenaline- and alloxan-induced diabetic rats in vivo. In addition, the strain exhibited in vitro α-amylase inhibiting effects, as well as reduced oxidative stress in the liver and the pancreas of alloxan-induced diabetic rats. Based on these studies, it is believed that food supplements of specific lactic acid bacteria strains can be effective as a preventive strategy against metabolic disorders. However, further long-term studies are needed to validate the specific constituents and, thus, the mechanisms responsible for the hypoglycemia-reducing effect of L. kunkeei.